Defining the phenotypical spectrum associated with variants in TUBB2A. Issue 1 (22nd June 2020) - Brock, Stefanie; Vanderhasselt, Tim; Vermaning, Sietske; Keymolen, Kathelijn; Régal, Luc; Romaniello, Romina; Wieczorek, Dagmar; Storm, Tim Matthias; Schaeferhoff, Karin; Hehr, Ute; Kuechler, Alma; Krägeloh-Mann, Ingeborg; et al.
Abstract : Background: Variants in genes belonging to the tubulin superfamily account for a heterogeneous spectrum of brain malformations referred to as tubulinopathies. Variants in TUBB2A have been reported in 10 patients with a broad spectrum of brain imaging features, ranging from a normal cortex to polymicrogyria, while one patient has been reported with progressive atrophy of the cerebellar vermis. Methods: In order to further refine the phenotypical spectrum associated with TUBB2A, clinical and imaging features of 12 patients with pathogenic TUBB2A variants, recruited via the international network of the authors, were reviewed. Results: We report 12 patients with eight novel and one recurrent variants spread throughout the TUBB2A gene but encoding for amino acids clustering at the protein surface. Eleven patients (91.7%) developed seizures in early life. All patients suffered from intellectual disability, and 11 patients had severe motor developmental delay, with 4 patients (36.4 %) being non-ambulatory. The cerebral cortex was normal in five individuals and showed dysgyria of variable severity in seven patients. Associated brain malformations were less frequent in TUBB2A patients compared with other tubulinopathies. None of the patients had progressive cerebellar atrophy. Conclusion: The imaging phenotype associated with pathogenic variants in TUBB2A is highly variable, ranging from a normal cortex to extensive dysgyria with associated brain malformations. For recurrent variants, no clear genotype–phenotype correlations could be established, suggesting the role of additional modifiers.